2013
DOI: 10.1002/gcc.22076
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide identification of genes with amplification and/or fusion in small cell lung cancer

Abstract: To obtain a landscape of gross genetic alterations in small cell lung cancer (SCLC), genome-wide copy number analysis and whole-transcriptome sequencing were performed in 58 and 42 SCLCs, respectively. Focal amplification of known oncogene loci, MYCL1 (1p34.2), MYCN (2p24.3), and MYC (8q24.21), was frequently and mutually exclusively detected. MYCL1 and MYC were co-amplified with other regions on either the same or the different chromosome in several cases. In addition, the 9p24.1 region was identified as bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 43 publications
(68 reference statements)
6
101
1
Order By: Relevance
“…4A). Codeletion of PTEN was not observed in the SCLC tumors with KAT6B genomic loss according to CNV microarray data (36). Interestingly, screening for nonsense and indels in the KAT6B coding sequence in these 60 SLC cases, we identified a deletion of a "C" in the last exon (exon 18; c.3824delC) that later creates a stop codon and renders a 798 amino acids shorter protein, suggesting alternative pathways for the inactivation of the studied gene.…”
Section: Nci-n417 Shrna8mentioning
confidence: 81%
“…4A). Codeletion of PTEN was not observed in the SCLC tumors with KAT6B genomic loss according to CNV microarray data (36). Interestingly, screening for nonsense and indels in the KAT6B coding sequence in these 60 SLC cases, we identified a deletion of a "C" in the last exon (exon 18; c.3824delC) that later creates a stop codon and renders a 798 amino acids shorter protein, suggesting alternative pathways for the inactivation of the studied gene.…”
Section: Nci-n417 Shrna8mentioning
confidence: 81%
“…In a recent survey of 4934 cancers from TCGA, Zack et al (2013) employed multiple criteria to model chromothripsis by SNP array copy number alone and suggested that chromothripsis occurred in 5% of all samples, with frequencies ranging from 0% in head and neck squamous carcinoma to a maximum of 16% in glioblastoma. In addition, chromothripsis has been observed in colorectal cancer (Kloosterman et al 2011b), melanoma (Berger et al 2012;Hammond et al 2013;Hirsch et al 2013), small-cell lung cancer (Iwakawa et al 2013), prostate cancer (Wu et al 2012), and a variety of brain tumors (Molenaar et al 2012;Northcott et al 2012;Brastianos et al 2013) and blood malignancies (MacKinnon and Campbell 2013;Morin et al 2013;Nagel et al 2013). It is interesting to point out that the rate of chromothripsis seems to be unrelated to the overall rate of somatic copy number alterations (SCNAs) (Zack et al 2013).…”
Section: How Frequently Does Chromothripsis Happen?mentioning
confidence: 99%
“…Having recognized the association between chromothripsis, double minutes, and cancer-causing mutations, one can infer chromothripsis as the most likely underlying mechanism in the formation of high-level focal amplifications that incorporate multiple disconnected segments (Iwakawa et al 2013;Sanborn et al 2013). The multiple focal amplifications can be either extrachromosomal (double minutes) or intrachromosomal (homogeneously staining regions [HSRs]) due to chromosomal integration of double minutes (Storlazzi et al 2010;Gibaud et al 2013).…”
Section: Does Chromothripsis Cause Cancer?mentioning
confidence: 99%
“…Unlike therapy for lung adenocarcinoma (LADC), the treatment for SCLC has not significantly advanced over the last three decades (2)(3)(4). To understand the genomic landscape and identify candidate therapeutic targets in SCLC, large-scale genomic analyses were performed, which revealed that mutations in TP53 and RB1, and amplifications of the MYC family members SOX2 and SRSF1, have been recurrently identified (5)(6)(7)(8). Although it was reported that somatic genomic rearrangements of TP73 contribute to SCLC tumorigenesis (5), druggable gene aberrations are rarely identified.…”
Section: Introductionmentioning
confidence: 99%